2015
DOI: 10.1021/am507193a
|View full text |Cite
|
Sign up to set email alerts
|

Transfection System of Amino-Functionalized Calcium Phosphate Nanoparticles: In Vitro Efficacy, Biodegradability, and Immunogenicity Study

Abstract: Many methods have been developed in order to use calcium phosphate (CaP) for delivering nucleotides into living cells. Surface functionalization of CaP nanoparticles (CaP NPs) with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane was shown recently to achieve dispersed NPs with a positive surface charge, capable of transfection (Chem. Mater. 2013, 25 (18), 3667). In this study, different crystal structures of amino-modified CaP NPs (brushite and hydroxyapatite) were investigated for their interaction in cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The shape of NPs has also been demonstrated to affect interactions with the innate immune system [21,25,36]. Groll et al found that the uptake of nanorods by macrophages was more efficient than the uptake of nanospheres.…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%
“…The shape of NPs has also been demonstrated to affect interactions with the innate immune system [21,25,36]. Groll et al found that the uptake of nanorods by macrophages was more efficient than the uptake of nanospheres.…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%
“…However, a preliminary study regarding their effect on the activation of complement system was conducted to have a clearer understanding in this regard. C3a complement activation assay, which was conducted according to a standard protocol mentioned in previous studies, can give some first idea as to what extent the bacteriabots can lead to complement‐activated clearance and trigger immune system. It was already known that the E. coli bacteria can induce the complement system, but the synergic behavior after attaching to microparticles is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Immune responses, inflammatory reactions and phagocytosis have been demonstrated by NCs, such as iron oxide NCs 365, 366 . Additionally, cytotoxicity of graphene quantum dots (GQDs) has led to a decrease in expression of the anti-apoptosis protein Bcl-2 and an increase in expression of pro-apoptotic proteins Bax and Bad 367 .…”
Section: - Nanotoxicologymentioning
confidence: 99%